Persepsi Guru SD Muhammadiyah 10 Tipes Surakarta Terhadap Penerapan Kurikulum 2013 - Arifianto, Dicky Adi; , Drs. Saring Marsudi, SH. M.Pd (2017)
ABSTRACT This research aims to: (1) Discribe How the perception of the teacher of Tipes 10 Muhammadiyah Elementary school of Surakarta about 2013 curriculum implementation, (2) Discribe how to preparation of 2013 curriculum implement, (3) Discribe the obstacles experienced by teacher of Tipes 10 Muhammadiyah Elementary School of Surakarta in implementing 2013 curriculum. This includes research into the qualitative descriptive study. Informants in this study were the head master, teacherof I and IV class of Tipes 10 Muhammadiyah Elementary School of Surakarta. The technique of data collection by way of interviews and documentation. The data were analyzed by means of the reduction of the data, the presentation of the data, and then draw conclusions. Techniques of examination of the validity of the data by using triangular sources and techniques. The results of this research showed that: (1) the teacher assess that the 2013 curriculum is a good curriculum to increase the liveliness of students in learning. (2) preparation which the teacher and headmaster carried out are following seminars and training both from Office and the outside, as well as complement the facilities and infrastructure in supporting learning. (3) Obstacles faced in implementing 2013 curriculum is the lack of time in the socialization and training as well as the large number of judgments to be made by the teacher for each student in learning. Keywords: Curriculum, 2013, the perception of teachers and principals.